The effect of irrigation solutions on the apical sealing ability in different root canal sealers - Emre Bodrumlu; Esra Parlak; Ebru Hazar Bodrumlu (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this study was to assess the effect of three root canal irrigation solutions on the apical sealing ability of three root canal obturation materials: gutta-percha/AH plus or MM-seal and Resilon/Epiphany SE. A total of 100 teeth with single straight root canals were randomly divided into three equal groups of 30 samples each, with the other 10 teeth (5 positive and 5 negative) used as controls. Each irrigation group was divided into three groups according to the use of three different root canal obturation materials (n = 10): Gutta-percha with AH plus or MM-seal, Resilon with Epiphany SE. The crowns were removed at the cementoenamel junction with a diamond disc under water coolant. The root canals were prepared using step-back technique and irrigation with either sodium hypochlorite (2.5%), chlorhexidine (2%), or MTAD solutions. The roots were obturated with lateral condensation technique using one of the obturation materials. The root surfaces was coated with two layer nail varnish (except apex), placed in 2% methylene blue dye solution, and centrifuged at 3,000 rpm for 5 minutes. Irrigation solutions affected the apical sealing ability of all the sealers. The chlorhexidine irrigation solution exhibited higher apical leakage values than did MTAD and NaOCl in all canal sealers, although the MTAD irrigation solution groups showed the least leakage values. The apical sealing ability of AH plus, Epiphany SE and MM-seal root canal sealers decreased when the chlorhexidine was used as an irrigation solution.